2006
DOI: 10.1007/s11195-006-9006-8
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Perceptions of Sexuality and HIV/AIDS among Young People with Physical Disabilities in a South African Township: a Case Study

Abstract: This study explored the experiences and perceptions of sexuality and HIV/ AIDS among 15-24 year-old young people with physical disabilities in a South African Township characterised by high unemployment rates and lack of social services. Ten young people and ten parents participated in multiple individual interviews as well as in focus group discussions. The analysis of audio taped and transcribed responses identified common experiences and perceptions among participants. The results indicate that disabled you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 13 publications
2
27
0
Order By: Relevance
“…Surveys and interview studies of people with disabilities and staff or key informants suggest generally low levels of HIV knowledge for people with disabilities (Bat-Chava et al, 2005;Chopra et al, 1998;Chuang & Atkinson, 1996;Dawood et al, 2006;de Andrade & Baloyi B, 2010;Doyle, 1995;Enwereji & Enwereji, 2008;Goldstein et al, 2010;Gordon et al, 1999;Hughes & Gray, 2009;Luckner & Gonzales, 1993;Melo et al, 2010;Otto-Salaj et al, 1998;Philander & Swartz, 2006;Strauss et al, 2006;Wazakili et al, 2006;Wazakili et al, 2009;Yousafzai et al, 2005), however, few of these studies involved control groups against which levels of knowledge could be compared. In studies that did compare people with disabilities to a sample of non-disabled peers, results indicated significantly lower levels of HIV knowledge (Bisol et al, 2008;Grassi et al, 1999a;Groce et al, 2006;Groce et al, 2007;Heuttel & Rothstein, 2001;Katz et al, 1994;Koen et al, 2007a;McGillivray, 1999;Ogunsemi et al, 2006;Otte et al, 2008;Rurangirwa et al, 2006;Yousafzai et al, 2004).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Surveys and interview studies of people with disabilities and staff or key informants suggest generally low levels of HIV knowledge for people with disabilities (Bat-Chava et al, 2005;Chopra et al, 1998;Chuang & Atkinson, 1996;Dawood et al, 2006;de Andrade & Baloyi B, 2010;Doyle, 1995;Enwereji & Enwereji, 2008;Goldstein et al, 2010;Gordon et al, 1999;Hughes & Gray, 2009;Luckner & Gonzales, 1993;Melo et al, 2010;Otto-Salaj et al, 1998;Philander & Swartz, 2006;Strauss et al, 2006;Wazakili et al, 2006;Wazakili et al, 2009;Yousafzai et al, 2005), however, few of these studies involved control groups against which levels of knowledge could be compared. In studies that did compare people with disabilities to a sample of non-disabled peers, results indicated significantly lower levels of HIV knowledge (Bisol et al, 2008;Grassi et al, 1999a;Groce et al, 2006;Groce et al, 2007;Heuttel & Rothstein, 2001;Katz et al, 1994;Koen et al, 2007a;McGillivray, 1999;Ogunsemi et al, 2006;Otte et al, 2008;Rurangirwa et al, 2006;Yousafzai et al, 2004).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In South Africa, the few studies which have been F o r P e e r R e v i e w 4 conducted suggest that knowledge about HIV/AIDS among people with disabilities is low [8][9]. Findings from other parts of the world suggest that people with disabilities have lower levels of HIV-related knowledge compared to the general population [10][11].…”
mentioning
confidence: 99%
“…As previously noted, a study carried out by Wazakili, Mpofu, and Devlieger (2006) in a South African township revealed that in some instances the desire of disabled people to be accepted and to be loved may supersede the importance of engaging in safe sexual practices.…”
Section: Aidsmentioning
confidence: 90%
“…However, Wazakili, Mpofu, and Devlieger (2006) better to have the information and to decide not to use it than not to have it at all. The idea is to ensure that sexuality and HIV information and services are accessible to all human beings in order to reduce the risk of acquiring HIV, which I discuss in the following sub-theme.…”
Section: Just Agreed To Have Sex With Him But I Knew That He Has Aimentioning
confidence: 99%
See 1 more Smart Citation